2011
DOI: 10.1111/j.1365-2362.2011.02517.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine metabolic side effects: association with the WNK4 system

Abstract: These observations may explain in part the mechanism of cyclosporine-induced hypertension, hyperkalemia and hypercalciuria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 33 publications
4
42
0
3
Order By: Relevance
“…Although cyclosporine and tacrolimus have different intracellular binding proteins, they both activate NCC, and this effect therefore appears to be a class effect [45]. Again, cyclosporine and tacrolimus do not seem to activate NCC directly, but influence the WNKs [76]. This possibility was already suggested by the side-effect profile of these drugs, which is similar to the phenotype of FHHt.…”
Section: Drugs Stimulating Nccsupporting
confidence: 49%
See 2 more Smart Citations
“…Although cyclosporine and tacrolimus have different intracellular binding proteins, they both activate NCC, and this effect therefore appears to be a class effect [45]. Again, cyclosporine and tacrolimus do not seem to activate NCC directly, but influence the WNKs [76]. This possibility was already suggested by the side-effect profile of these drugs, which is similar to the phenotype of FHHt.…”
Section: Drugs Stimulating Nccsupporting
confidence: 49%
“…To fully grasp the potential of these insights for the treatment of human disease will likely require a more complete understanding of the molecular physiology of this fascinating cotransporter. Footnote: ¶ When high dietary K increases aldosterone, NCC may be inhibited; * Some of these effects may be mediated through aldosterone; † In a model of cyclosporine nephrotoxicity , 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 23 NCC was downregulated, but this may be attributed to kidney failure and reduced reninangiotensin activity [76]. …”
Section: Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of these drugs is associated with an increased hypertension rate and two groups have observed that tacrolimus (56) and cyclosporine (78) in rodents induce phosphorylation and activation of NCC, thus increasing salt reabsorption and hypertension. Inhibition of the phosphatase calcineurin and, thus, prevention of NCC dephosphorylation is the likely mechanism because elimination of the FKBP12-binding protein along the nephron precluded the hypertensive effect of this compound; this protein is required for the tacrolimus inhibition of calcineurin (65).…”
Section: F137 Slc12 Cotransporters In the Kidneymentioning
confidence: 99%
“…Cyclosporine is also known to cause a combination of metabolic side effects including hypertension, hyperkalemia, hypercalciuria and hypomagnesemia. To overcome the drawback it has been reported to minimize the dosage or to limit the duration of therapy [39,40]. The ability of CsA to increase nerve regeneration in vivo is reported to be dose-related the rat in systemic administration [18].…”
Section: Discussionmentioning
confidence: 99%